Homology, Collective and Cultural Memory: Augustus’ Portraiture and Augustan Poetry - Martins, Paulo (Revista Archai, 2025)
This paper aims to establish a homology between two forms of art: the portraits of Octavian Augustus and Augustan poetry, particularly the works of Horace, Ovid, Propertius, and Virgil. The theoretical frameworks of Nora (<a href="https://www.scielo.br/j/archai/a/Sjf7CmHKyCB4RW5crKGCjRv/?lang=en#B45_ref" data-ref="NORA, P. (1989). Between Memory and History: Les Lieux de Mémoire. Representations 26, p. 7-24. https://doi.org/10.2307/2928520.">1989), Assmann (<a href="https://www.scielo.br/j/archai/a/Sjf7CmHKyCB4RW5crKGCjRv/?lang=en#B4_ref" data-ref="ASSMANN, J. (1995). Collective Memory and Cultural Identity. New German Critique 65, p. 125-33. DOI: 102307/488538.">1995 and <a href="https://www.scielo.br/j/archai/a/Sjf7CmHKyCB4RW5crKGCjRv/?lang=en#B5_ref" data-ref="ASSMANN, J. (2011). Cultural memory and early civilization: writing, remembrance, and political imagination. Cambridge, Cambridge University Press. ">2011), Halbwachs (1968), and Galinsky (<a href="https://www.scielo.br/j/archai/a/Sjf7CmHKyCB4RW5crKGCjRv/?lang=en#B22_ref" data-ref="GALINSKY, K., ed. (2014). Memoria Romana. Memory in Rome and Rome in Memory. Ann Harbor, University of Michigan Press. ">2014-<a href="https://www.scielo.br/j/archai/a/Sjf7CmHKyCB4RW5crKGCjRv/?lang=en#B24_ref" data-ref="GALINSKY, K.; LAPATIN, K. (eds.). (2016). Cultural Memories in the Roman Empire. Los Angeles, J. Paul Getty Museum. ">2016) are mobilized to support the argument that both artistic expressions can be interpreted as vehicles of collective memory and cultural memory, serving the perpetuation of power and art